CYP1A1 and GSTM1 genotypes affect benzo[a]pyrene DNA adducts in smokers' lung: comparison with aromatic/hydrophobic adduct formation - Alexandrov, Kroum; Bartsch, Helmut (Carcinogenesis, 2002)
Abstract. Benzo[ a ]pyrene diol epoxide (BPDE)-DNA adducts are involved in the induction of p53 mutations and probably in the causation of human lung cancer ass